2022
DOI: 10.1038/s41598-022-12081-z
|View full text |Cite
|
Sign up to set email alerts
|

Probing the effect of Ni, Co and Fe doping concentrations on the antibacterial behaviors of MgO nanoparticles

Abstract: The divalent transition metal ions (Ni, Co, and Fe)-doped MgO nanoparticles were synthesized via the sol–gel method. X-ray diffraction showed the MgO pure, single cubic phase of samples at 600 °C. Field emission electron microscope showed the uniform spherical shape of samples. The magnetic behavior of Ni, Co, Fe-doped MgO system were varied with Ni, Co, Fe content (0.00, 0.01, 0.03, 0.05, 0.07). The magnetic nature of pure had changed from paramagnetic to ferromagnetic. The number of oxygen vacancies increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 78 publications
0
18
1
Order By: Relevance
“…15 The peaks of MgO at 42.7° and 62.1° are ascribed to (200) and (220) of cubic structures. 16 It was observed that the MgO addition influences the exposed planes of ZnO crystals. The CuO peaks at 35.5° and 38.7° shifted towards a higher angle for CuZnMg (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…15 The peaks of MgO at 42.7° and 62.1° are ascribed to (200) and (220) of cubic structures. 16 It was observed that the MgO addition influences the exposed planes of ZnO crystals. The CuO peaks at 35.5° and 38.7° shifted towards a higher angle for CuZnMg (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Ranathunge et al [ 41 ] investigated pure MgO NPs ( d = 20 nm) for application in cancer therapy. Recently, Almontasser and Parveen [ 42 ] studied Ni, Co and Fe-doped MgO NPs for biomedical applications.…”
Section: Numerical Results and Discussionmentioning
confidence: 99%
“…Ranathunge et al [ 41 ] developed pure MgO nanoflakes ( d = 20 nm) as drug carriers and loaded them with doxorubicin for use as a targeted drug-delivery system for potential application in cancer therapy. Recently, Almontasser and Parveen [ 42 ] studied the effects of Ni, Co and Fe doping concentrations on the antibacterial behaviors of MgO NPs for biomedical applications. The number of oxygen vacancies increases with increasing amounts of dopant ions, leading to an increase in magnetic properties.…”
Section: Introductionmentioning
confidence: 99%
“…Metal NPs (NPs) are metals with a density of more than 5 g/cm 3 [ 40 ]. Al (Al 2 O 3 ), Au, Bi, Ce, Cu (CuI, CuO, and Cu 2 O), Fe (Fe 2 O 3 ), Mg (MgO), Ti (TiO 2 ), and Zn (ZnO) are metals that are fabricated to synthesize NPs [ 41 , 42 , 43 , 44 ] which are small in size and have a high surface-to-volume ratio, which impacts the antibacterial activity of NPs [ 40 ].…”
Section: Metal Nanoparticlesmentioning
confidence: 99%
“…Gold nano-particles (AuNPs) have been reported to revert MRSA resistance [ 42 ]. This study investigated attachment of amoxicillin to AuNPs in inhibiting clinical isolates and surmised an enhanced antibacterial efficacy.…”
Section: Prospects Of Metal-containing Nps In Treating Mrsamentioning
confidence: 99%